Reservoir operation rules for controlling algal blooms in a tributary to the impoundment of Three Gorges Dam - Lian, Jijian (IAHR, 2020)
Since the first impoundment of Three Gorges Dam in 2003, algal blooms occur frequently in the near-dam tributaries. An attempt is made in our study to develop reservoir operation rules that would reduce the level of algal blooms in the near-dam tributaries. The reservoir operations can further increase the water exchange between the mainstream of the Three Gorges Reservoir and the Xiangxi River tributary and thus move a larger amount of algae into the deep water where it would die. Analysis of the model results indicated that water is charge fluctuations consisting of a lower night-time valley-load flow and a larger flow component to satisfy daytime peak load during short-term operations (within a day), the rise in water level during the medium-term operation (e.g., over weeks), and the combination of these two during the long-term operation (e.g., over months) can provide feasible reservoir operation rules in the non-flood season for TGR.